Research on the Method of Depth Peaking at Full Load of Supercritical Circulating Fluidized Bed Unit - Bin NIU; Lifeng LI; Qian SUN; Peihua ZHANG (发电技术)
With the expansion of installed capacity of new energy power generation, the thermal power market has been severely squeezed. To meet the needs of grid flexibility, thermal power plants are required to undertake the task of deep peak shaving. Circulating fluidized bed units can be used without shutdown. It takes a supercritical 350MW circulating fluidized bed unit in a power plant in Shanxi Province as the research object. Two kinds of deep peak shaving methods of supercritical circulating fluidized bed unit's typical steam-water systems were analyzed. Some problems that might be encountered during operation were analyzed. Corresponding prevention and control measures were provided. Finally, the analysis shows that the supercritical circulating fluidized bed unit can use two typical steam-water systems to achieve full load deep peak shaving. The investment of adding boiler water circulating pump system is large, and the operation is complex. The investment of adding water storage tank to deaerator pipeline is small, and the operation is simple. However, when the boiler water circulating pump system is added to participate in full load deep peak shaving, the stability of each system is better.